1996
DOI: 10.1016/s0029-5493(96)01254-x
|View full text |Cite
|
Sign up to set email alerts
|

Aging management of containment structures in nuclear power plants

Abstract: Research swnsored by the Office oi Suciur Keguiatow Research. U.S. Suclear Regulatory Comnussmn under inrcngency Agreement 1886--8084-5B w~t h the U.S. D e p m e n t or E n s 9 under Conuact DE-AC05-840R21400. Acwtdmgly. the U.S. (jovemrnent retams a nonexcluslve. royally-iree hcense IO pubhsh or reomuce the published form oi this mnmbutlon, or allow olhers to do $0, ior L.S. Government purposes.h e submitted rnanuscnpt has k e n aumorrd bv a contractor of the C.S. Government under Conma lio. DE-ACOS-840F2.140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In nuclear power generating facilities, RSC has been used for containment structures lined with steel surrounding a reactor or steam generator [ 8 ]. RSC that is used to protect a reactor needs to have a high content of heavyweight coarse aggregate to attenuate radiation [ 7 ]. For the secondary containment, which includes the steam generator, prestressed concrete is required to contain the high pressure generated from the pressurized steam generator [ 8 ].…”
Section: Classifications and Major Functions Of Rscmentioning
confidence: 99%
See 3 more Smart Citations
“…In nuclear power generating facilities, RSC has been used for containment structures lined with steel surrounding a reactor or steam generator [ 8 ]. RSC that is used to protect a reactor needs to have a high content of heavyweight coarse aggregate to attenuate radiation [ 7 ]. For the secondary containment, which includes the steam generator, prestressed concrete is required to contain the high pressure generated from the pressurized steam generator [ 8 ].…”
Section: Classifications and Major Functions Of Rscmentioning
confidence: 99%
“…The composition of RSC is mostly similar to that of conventional concrete except for its aggregates. Certain RSCs incorporate a heavyweight aggregate to improve their radiation shielding property, hence requiring less thickness for a containment structure [ 7 ]. Similar to conventional concrete, RSC is made of a binder, aggregate, and additive.…”
Section: Alternative Materials Used In Rscmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there have been several instances where the capacity of the containment or other safety-related structures has been challenged by sources of degradation. A questionnaire was sent to U.S. utilities concerning inspection, degradation and repair of reinforced concrete structures in light-water reactor plants (Naus, et al 1994). Responses provided by 29 utilities representing 41 units revealed that the majority of plants are inspected visually only in compliance with integrated-leak rate tests and surveillance of post-tensioning systems as required by RG 1.…”
Section: Nuleg/cr-6425mentioning
confidence: 99%